Alteration of the QT variability index in end-stage liver disease - Huh, In Young; Park, Eun Sun; Kim, Kang-Il; Lee, A-Ran; Hwang, Gyu-Sam (Korean journal of anesthesiology, 2014)
A prolonged QT interval can lead to malignant ventricular arrhythmias and sudden cardiac death, and has frequently been found in end-stage liver disease (ESLD). However, myocardial repolarization lability has not yet been fully investigated. We evaluated the QT variability index (QTVI), a marker of temporal inhomogeneity in ventricular repolarization and an abnormality associated with re-entrant malignant ventricular arrhythmias. We determined whether QTVI is affected by the head-up tilt test in ESLD. We assessed 36 ESLD patients and 12 control subjects without overt heart disease before and after the 70-degree head-up tilt test. The electrocardiography signal (lead II) was recorded on a computer with an analog-to-digital converter. The RR interval (RRI) and QT interval were measured after recording 5 min of the digitized electrocardiography. Then, the QT intervals were corrected with Bazett's formula (QTc). QTVI was calculated through the following formula: QTVI = log10 [(QTv/QTm2)/(RRIv/RRIm2)], QTv/RRIv: variance of QTI/RRI, QTm/RRIm: mean of QT interval/RRI. Cirrhotic patients exhibited an elevated QTVI. In particular, Child class C patients had a significantly increased QTVI compared to Child class A patients and the control subjects in the supine position. However, the head-up tilt test did not cause a significant difference in QTVI in relation to the severity of ESLD. Myocardial repolarization lability was significantly altered in end-stage liver disease. Our data suggest that the severity of ESLD is associated with the degree of the alteration in the QT variability index.